Implementasi Moderasi Beragama Di Dusun Ceto Kabupaten Karanganyar - Davit Eko Prasetyo; Setyaningsih; Made Sukarsih (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
This research seeks to identify how religious moderation implementation, the factors influencing the formation of religious moderation, and the implications of religious moderation in the community life of Ceto Hamlet, Gumeng Village, Jenawi District, Karanganyar Regency. Ceto Hamlet is a multireligious area where Hindu, Muslim, and Christian communities live side by side harmoniously. The research employed a qualitative approach that included descriptive methods. Data was gathered using techniques such as observation, interviews, and document analysis. The participants in this research consisted of religious leaders, community leaders, village officials, youth organizations, and local residents of Ceto Hamlet. The analysis of data involved stages of data reduction, presentation of findings, and concluding observations. Findings revealed that the execution of religious moderation in Ceto Hamlet is notable. This research aims that the implementation of religious moderation in Ceto Hamlet is reflected in interfaith tolerance practices, social cooperation, mutual assistance, and community participation in religious and traditional activities without distinguishing religious backgrounds. The factors influencing the formation of religious moderation include local wisdom, a culture of mutual cooperation, the role of religious and community leaders, and the collective awareness of the community formed through long-term shared living experiences. The implementation of religious moderation has positive implications for creating social harmony, shaping tolerant community character, and maintaining the sustainability of peaceful and harmonious multireligious life in Ceto Hamlet.